Fluid-structure interaction study of gas turbine blade vibrations - Forbes, Gareth; Alshroof, O.; Randall, R. (Engineers Media for Engineers Australia, 2011)
A recent research program has identified the possibility of using the analysis of casing wall pressures in the direct measurement of gas turbine rotor blade vibration amplitudes. Currently the dominant method of non-contact measurement of gas turbine blade vibrations employs the use of a number of proximity probes located around the engine periphery measuring the blade tip (arrival) time. Despite the increasing ability of this method there still exist some limitations, ie. the requirement of a large number of sensors for each engine stage, sensitivity to sensor location, difficulties in dealing with multiple excitation frequencies and sensors being located in the gas path. Analytical modelling of the casing wall pressures and reconstruction of rotor blade vibration amplitudes from the analysis of these simulated pressure signals has shown significant improvement over current non-contact rotor blade vibration measurement limitations by requiring only a limited number of sensors and providing robust rotor blade vibration amplitude estimates in the presence of simulated measurement noise. However, this modelling was conducted with some fundamental assumptions about the casing wall pressures being made.One of these assumptions presumed that during blade motion the pressure profile around the rotor blades follows the blade's motion while it oscillates around its equilibrium position. This assumption is investigated in this paper through the numerical modelling of the fully coupled two-way rotor blade motion and fluid pressure interaction.